Analisis Strategi Perencanaan Pesan pada Akun Instagram E-commerce @thekufed - Widya Putri, Dhita; Mormes, Maulida De (Universitas Semarang, 2017)
Instagram is a social media that has a visual power. Together with, many parties both individuals and organizations use Instagram to get some information they want to convey. For instance, PT. Hood Digital Asia (Kufed) who created @thekufed account to develop their messages that will be delivered to their publics. They used their own strategy by adjusting the characters and the concepts with their targets. Therefore, this study explored about how @thekufed designed their messages strategy. The researcher used qualitative method with descriptive approach to examine Kufed s message plan and strategy, such as teaser, community building, collaboration with influencers for content production and curation of products, as well as planning the story to strengthen the visual content with emotionless. The conclusion is Kufed has implemented the message strategy based on its concept and character.